People, Technology, and Culture: Relationship Transformation in The Digital Era - Tanjung, Desy Rahmadani; Santosa, Alif (International Journal of Students Education, 2023)
This article aims to discuss in more depth the transformation of the relationship between humans, technology and culture in the digital era. The research method used in this research is a literature review method. The digital era has inspired a deep transformation in human relations, technology and culture. The development of information and communication technology not only modernizes the way we work and communicate, but also shapes cultural dynamics that change the essence of everyday life. Online identities and intensive engagement in social media have become integral elements in shaping cultural narratives, strengthening global connections, and opening the door to a more inclusive cultural essence. While these changes bring significant opportunities and progress, challenges arise. The continuity of traditional cultural values, generational gaps in adaptation to technology, and privacy issues are points that need serious attention. Striking a balance between sharing an online identity and protecting personal privacy is a delicate task in an era where the boundaries between online and offline life are increasingly blurred. Reflections on cultural change highlight the complexity of these dynamics, inviting us to evaluate the impact of technology on our values, the way we interact, and the way we understand cultural identity. As a society in the digital era, it is important for us to bring deeper awareness, recognize and manage change wisely. With this awareness, we can direct this transformation in a more positive and sustainable direction. By combining technology with a deep understanding of cultural values, we can shape a digital era that respects diversity, strengthens closeness between people, and maintains human values amidst rapid change. That way, we can embrace the digital era as a milestone for progress, while still adhering to the cultural wisdom inherent in human diversity.